2016
DOI: 10.1371/journal.pone.0163716
|View full text |Cite|
|
Sign up to set email alerts
|

Lack of Effect of Oral Sulforaphane Administration on Nrf2 Expression in COPD: A Randomized, Double-Blind, Placebo Controlled Trial

Abstract: BackgroundCOPD patients have high pulmonary and systemic oxidative stress that correlates with severity of disease. Sulforaphane has been shown to induce expression of antioxidant genes via activation of a transcription factor, nuclear factor erythroid-2 related factor 2 (Nrf2).MethodsThis parallel, placebo-controlled, phase 2, randomized trial was conducted at three US academic medical centers. Patients who met GOLD criteria for COPD and were able to tolerate bronchoscopies were randomly assigned (1:1:1) to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(83 citation statements)
references
References 28 publications
4
79
0
Order By: Relevance
“…The Nrf2 activating molecule sulforaphane improves phagocytosis of bacteria in alveolar macrophages of patients with COPD [37]. A 4 week clinical trial of sulforaphane did not increase Nrf2 target gene expression, decrease markers of oxidative stress or improve lung function in patients with COPD [38]. The Nrf2 activator dimethyl fumarate (BG-12), which is approved in the US for the treatment of multiple sclerosis [39] is undergoing investigation in an inhaled microparticulate powder formulation for the treatment of respiratory disorders [40], but currently no clinical studies are underway in COPD or IPF [41].…”
Section: Nuclear Erythroid-2 Related Factor 2 Activatorsmentioning
confidence: 98%
“…The Nrf2 activating molecule sulforaphane improves phagocytosis of bacteria in alveolar macrophages of patients with COPD [37]. A 4 week clinical trial of sulforaphane did not increase Nrf2 target gene expression, decrease markers of oxidative stress or improve lung function in patients with COPD [38]. The Nrf2 activator dimethyl fumarate (BG-12), which is approved in the US for the treatment of multiple sclerosis [39] is undergoing investigation in an inhaled microparticulate powder formulation for the treatment of respiratory disorders [40], but currently no clinical studies are underway in COPD or IPF [41].…”
Section: Nuclear Erythroid-2 Related Factor 2 Activatorsmentioning
confidence: 98%
“…Within the short-term studies (Table S1), we found two documents on prostate [39] and melanoma [40], three papers on respiratory pathologies [41][42][43], and one on type 2 diabetes [44]. The main limitation observed in these studies is the length or duration of the study, of 1 month or less, because the validity of the data in terms of changes in bioavailability of the intake of compounds could be acceptable, but for the evaluation of data from tissues, the time of exposition is too low.…”
Section: Short-time Studiesmentioning
confidence: 99%
“…The work of Wise et al [42], compared to the previous one, increased the time of intervention, but again used a supplement-capsules with different concentrations of SFN. The pathology under study was chronic obstructive pulmonary disease (COPD), and in both cases, asthma and COPD were obstructive conditions.…”
Section: Short-time Studiesmentioning
confidence: 99%
“…For exposure indicator, urinary glutathione conjugates of ITCs are usually used but those have to be collected within 12 h to achieve a quantifiable range. Many of the “proof‐of‐concept” studies could not demonstrate that sufficient ITCs were absorbed to induce molecular targets in a threshold or dose‐response manner, future studies need to optimize methods for quantification of exposure. In regard to early response indicators, they need to be linked to dietary compounds through biological mechanisms as well as to the cancer endpoint.…”
Section: Clinical Studies Of Cruciferous Vegetable or Itc Intake For mentioning
confidence: 99%